Are Policy Analogies Persuasive? The Household Budget Analogy and Public Support for Austerity. Issue 3 (8th July 2022) - Barnes, Lucy; Hicks, Timothy
Abstract: Public opinion on complex policy questions is shaped by the ways in which elites simplify the issues. Given the prevalence of metaphor and analogy as tools for cognitive problem solving, the deployment of analogies is often proposed as a tool for this kind of influence. For instance, a prominent explanation for the acceptance of austerity is that voters understand government deficits through an analogy to household borrowing. Indeed, there are theoretical reasons to think the household finance analogy represents a most likely case for the causal influence of analogical reasoning on policy preferences. This article examines this best-case scenario using original survey data from the United Kingdom. It reports observational and experimental analyses that find no evidence of causation running from the household analogy to preferences over the government budget. Rather, endorsement of the analogy is invoked ex post to justify support for fiscal consolidation.